Light energy dissipation in Quercus ilex resprouts after fire (AUSTRALIAN JOURNAL OF PLANT PHYSIOLOGY, 2000)
Holm oak (Quercus ilex) plants that have resprouted after fire have higher photosynthetic capacity than control plants in intact vegetation. In this study, branches detached from forest plants were fed with dithiothreitol (DTT) in the laboratory to inhibit zeaxanthin production and thus reduce the dissipation of light energy as heat. This allowed us to test the hypothesis that plants with greater photosynthetic capacity, and therefore greater photochemical sink strength, would suffer a lower reduction in photochemical efficiency under stressful conditions. Greater rates of photochemistry in resprouts, which exhibited increased photosynthesis (A), leaf conductance (g), quantum yield of PSII (Delta F/F-m') and photochemical quenching (q(P)), were related to lower non-radiative dissipation of excess energy as indicated by 1 - (F-v'/F-m'). However, the fraction of energy remaining of that used in photochemistry or dissipated thermally in the PSII antennae was similar in resprouts and controls and was not affected by DTT, especially under high irradiance conditions. Zeaxanthin involvement in PSII protection operated in resprouts and controls since DTT induced the same kind of response (NPQ decrease) but was lower in resprouts. These chlorophyll fluorescence results suggest the participation of some additional mechanism for energy dissipation. Light capture characteristics of the photosynthetic apparatus did not differ between resprouts and controls, and leaf age did not play a determining role in the differences observed.
APS

Photosynthesis and photoprotection in Quercus ilex resprouts after fire (Tree Physiology, 1998)
Plants that resprout after fires often have higher rates of photosynthesis than before a fire. To elucidate the mechanism of this response, we studied gas exchange and chlorophyll fluorescence in Quercus ilex L. plants growing on control (unburned) sites and on sites that had been burned the preceding summer. In early July, photosynthetic rates and stomatal conductance were similar in plants on unburned and burned plots, and in young and old foliage within unburned plots. At this time, photochemical efficiency of photosystem II (PSII), nonphotochemical quenching of chlorophyll fluorescence (NPQ), and the de-epoxidation of violaxanthin to zeaxanthin were also similar among leaves of different ages and treatments. In late July, photosynthetic rates and stomatal conductances were much greater in resprouts on the burned areas than in unburned plants. From early to late July, unburned plants showed an increase in NPQ and the de-epoxidation of violaxanthin to zeaxanthin, indicating increased photoprotection as a result of enhanced nonradiative dissipation of excess light energy. Plants on the burned plots did not show these changes. Leaves of all ages and treatments showed no substantial reduction in potential quantum yield of PSII (Fv/Fm) at midday or predawn, indicating that there was little or no photoinhibition. Leaf nitrogen and soluble protein contents varied with leaf age during July, but did not vary between treatments. We conclude that the primary effect of burning is an increase in water availability to resprouting plants that eliminates the need for photoprotection, at least in the short term. The decrease in photosynthetic rates of unburned leaves in late July was the result of reduced stomatal conductance. We suggest that lowered stomatal conductance is the primary limiting factor in Q. ilex leaves, governing the regulation of carboxylation activity and energy dissipation processes.
10.1093/treephys/18.8-9.607

Quercus ilex resprouts after fire: response to photoinhibition. (PLANT PHYSIOLOGY, 1997)
The study was located on Serra del Garraf mountains, Barcelona, NE Spain, overlooking the Mediterranian sea at 530 m. On August 1995 a wild fire consumed 100 hectares of the forest. In spring 1996 four plots were set (100 x
APS